2019
DOI: 10.3389/fpsyt.2019.00831
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Psychiatrist: In Search of Evidence-Based Apps for Anxiety and Depression

Abstract: One of the biggest growth areas in e-mental health resources has been the development and use of mobile mental health apps for smartphones and tablet devices. Such apps are being downloaded at increasing rates, but there have been questions about their efficacy and the research methodologies used to examine this. A review of the major app marketplaces, the Apple App Store and Google Play store, was conducted to locate apps claiming to offer a therapeutic treatment for depression and/or anxiety, and have resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 28 publications
1
63
0
3
Order By: Relevance
“…This is concerning, as most MH apps in app stores have little to no empirical backing. Approximately 3% of available depression and anxiety apps provide information regarding testing or effectiveness (Marshall et al 2019;Sucala et al 2017); when restricted to the 29 highest-rated depression apps, this rate only increased to 7% (Qu et al 2020). This has led to the development of multiple online libraries intending to curate effective MH apps (Marshall et al 2019).…”
Section: Skills Knowledge and Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is concerning, as most MH apps in app stores have little to no empirical backing. Approximately 3% of available depression and anxiety apps provide information regarding testing or effectiveness (Marshall et al 2019;Sucala et al 2017); when restricted to the 29 highest-rated depression apps, this rate only increased to 7% (Qu et al 2020). This has led to the development of multiple online libraries intending to curate effective MH apps (Marshall et al 2019).…”
Section: Skills Knowledge and Resourcesmentioning
confidence: 99%
“…This could involve collaborating with health agencies to (1) adopt stricter screening and acceptance policies and (2) require clear labeling of an app's developers, evidence base, indicated use, and privacy protections (Gordon et al 2020;Hidalgo-Mazzei et al 2020;Martinengo et al 2019;Stawarz et al 2018). In addition to benefiting the consumer, these changes may also benefit Apple and Google; modifying algorithms to elevate empirically supported MH apps to the front of the queue may lead to more downloads, as these apps may be more effective (Marshall et al 2019).…”
Section: External Contextmentioning
confidence: 99%
“…Pragmatic clinical trials could allow us to rapidly assess the association between digital interventions and outcomes in a real world context 3. Whereas randomised trials of traditional mental health interventions typically take years, recent studies using digital interventions have shown that they can be carried out among more than 1000 participants in a matter of weeks 4.…”
mentioning
confidence: 99%
“…There are several evidence-based frameworks that inform PTSD psychological treatments (as mentioned above), and it would seem plausible that such treatment interventions could be incorporated into an app. There needs to be expert input from qualified clinicians and/or researchers into the development of a mental health app-many apps claiming to treat symptoms of mental illness do not have such input (25,43,44). Given that the development of mobile mental health apps is still in its infancy, we are still not certain about the mechanisms of action of such apps, and therefore the level of importance of characteristics such as app design and usability is still being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…If the efficacy of mental health apps is to be free of the limitations affecting many drug trials, unbiased research is required while their development is still relatively young. In a recent review of the two major app stores, only 1% of apps that claimed to offer a therapeutic treatment for anxiety and depression had independent research to back-up claims of efficacy (25). That is, research that was conducted by individuals, institutions or organizations who were not involved in the development of the app, and who would not stand to gain financially or otherwise from it.…”
Section: The Evidence For Treating Symptoms Of Trauma With An Appmentioning
confidence: 99%